(untitled) (The Research of Medical Science Review, 2024)
To compare the efficacy of bathing with chlorhexidine and a control group to prevent the incidence of surgical site infection (SSI). This study was conducted at Islamabad Medical Complex, Islamabad, over a period of 3 months from 1st of March 2023 to 31st of May 2023.A total of 180 patients planned to undergo a surgical procedure and fulfilling the inclusion criteria were selected through consecutive sampling. Patients were divided in to 2 equal groups through computer generated sheet. In Group-A patients took a preoperative bath 3 hours before the surgical procedure with CHG 4% while Group-B patients took a routine preoperative bath without using any antiseptic agent. During the hospitalization period, surgical incision site was observed to find any sign of infection including redness of skin, pain around the incision wound or presence of purulent pus or fever. Patients was checked for SSI on day 3, followed up on day 10 and then telephonically contacted on day 20 and day 30 to find any sign of infection at site of surgery. Primary outcome was set as the number of patients remaining free of SSI up to 30 days follow up period. The mean age in this study was 34.92±7.10 years with an age range of 19-59 years. The male population in this study was 56.66% while the female population was 43.33%. The laboratory findings revealed that 76.11% of the patients had “Number of Microorganism Colonies >300”. The results of the study show that incidence of SSI was significantly lower in Group-A, 3 cases (3.33%) compared to Group-B, 13 cases (14.44%) (p=0.00). Preoperative bathing strategy with chlorhexidine prevents incidence of surgical site infection.